Dietary obesity reversibly induces synaptic stripping by microglia and impairs hippocampal plasticity - Hao, Shuai (Brain Behav Immun, 2015)
Obesity increases risk of age-related cognitive decline and is accompanied by peripheral inflammation. Studies in rodent models of obesity have demonstrated that impaired hippocampal function correlates with microglial activation, but the possibility that neuron/microglia interactions might be perturbed in obesity has never been directly examined. The goal of this study was to determine whether high fat diet-induced obesity promotes synaptic stripping by microglia, and whether any potential changes might be reversible by a return to low-fat diet (LFD). Time course experiments revealed that hippocampal inflammatory cytokine induction and loss of synaptic protein expression were detectable after three months of HFD, therefore subsequent groups of mice were maintained on HFD for three months before being switched to LFD for an additional two months on LFD (HFD/LFD). Additional HFD mice continued to receive HFD during this period (HFD/HFD), while another group of mice were maintained on LFD throughout the experiment (LFD/LFD). Dietary obesity impaired hippocampus-dependent memory, reduced long-term potentiation (LTP), and induced expression of the activation marker major histocompatibility complex II (MHCII) in hippocampal microglia. Diet reversal only partially attenuated increases in adiposity in HFD/LFD mice, but plasticity deficits and MHCII induction were normalized to within the range of LFD/LFD mice. Microglial activation and deficits in hippocampal function were accompanied by perturbation of spatial relationships between microglial processes and synaptic puncta. Analysis of primary microglia isolated from HFD/HFD mice revealed selective increases in internalization of synaptosomes labeled with a pH-sensitive fluorophore. Taken together, these findings indicate that dietary obesity reversibly impairs hippocampal function, and that deficits may be attributable to synaptic stripping by microglia.